ANALYSIS REFERENCE OF GRAMMATICAL COHESION TYPES IN NAWAL EL- SADAWI’S WOMAN AT POINT ZERO - Hablil Warid; hodairiyah hodairiyah; Ach Syariful Lail (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2021)
Abstract The researcher used the novel as the object of research with the title "Women at Point Zero" by Nawal El-Saadawi. This study aims to describe the type and function of the "reference of grammatical cohesion" used by Nawal El-Saadawi in her novel. In this study, the authors used Halliday's (1976) types of grammatical cohesion theory to analyze the types of reference of grammatical cohesion and describe the types of functions of the reference of grammatical cohesion. To support this research, the researcher used a qualitative method to analyze the words, phrases and sentences in this novel. Then the author describes in the form of a conclusion. The data is taken from a sentence that contains the types of references of grammatical cohesion in Nawal El-Saadawi's novel. The results of this study are reference includes: personal reference, demonstrative reference, definite article reference, comparative reference. The function of the reference of grammatical cohesion is "to avoid repetition of words", "to designate a close scale", and "to compare something or situation. Key words: Grammatical Cohesion, Reference, Nawal El- Sadawi’s Woman at Point Zero